Diagnostic accuracy of Raman spectroscopy in oral squamous cell carcinoma - Han, Ruiying; Lin, Nan; Huang, Juan; Ma, Xuelei (Frontiers in Oncology, 2022)
Background: Raman Spectroscopy (RS) has shown great potential in the diagnosis of oral squamous cell carcinoma (OSCC). Although many single-central original research has been carried out, it is difficult to use RS in real clinical settings based on the current limited evidence. Herein, we conducted this meta-analysis of diagnostic studies to evaluate the overall performance of RS in OSCC diagnosis. Methods: We systematic searched databases including Medline, EMBASE, and Web of Science for studies up to March 2022 with no start date limited. Data of true positives, true negatives, false positives and false negatives were extracted from the included studies to calculate the pooled sensitivity, specificity, accuracy, positive and negative likelihood ratios (LRs), and diagnostic odds ratio (DOR) with 95% confidence intervals, then we plotted the summary receiver operator characteristics (SROC) and the area under the curve (AUC) to evaluate the overall performance of Raman spectroscopy. Quality assessments and Publication bias were evaluated by QUADAS-2 checklist in Review Manager 5.3. The statistical parameters were calculated with StataSE version 12 and MetaDiSc 1.4. Results: Totally, 13 studies were included in our meta-analysis. The pooled diagnostic sensitivity and specificity of Raman Spectroscopy in OSCC were 0.89 (95% CI, 0.85–0.92) and 0.84 (95% CI, 0.78–0.89). The AUC of SROC curve was 0.93 (95% CI, 0.91–0.95). Conclusions: RS is a non-invasive diagnostic technology with high specificity and sensitivity for detecting OSCC and has the potential to be applied clinically.